DEVELOPMENT AND STABILITY EVALUATION OF ATORVASTATIN EXTEMPORANEOUS ORAL SUSPENSION FOR ELDERLY PATIENTS - KAEWPRADIT, SIRIKANYA; SIRIPITHAYA, YUWAKORN; JANTARAT, CHUTIMA (International Journal of Applied Pharmaceutics, 2025)
Objective: This study aims to develop an extemporaneous oral suspension formulation of atorvastatin (ATV) and evaluate its stability. Methods: ATV extemporaneous oral suspension was developed by preparation using different suspension vehicles. The developed formulation was stored at ambient temperature (30±2 °C) and refrigerated temperature (4±2 °C) to evaluate its physical and chemical stability. The formulation was also exposed to 3% hydrogen peroxide (H2O2), 1 M hydrochloric acid (HCl), and 1 M sodium hydroxide (NaOH) to evaluate its stability under stress conditions. ATV was analyzed using High-Performance Liquid Chromatography (HPLC), which was validated prior to use. Results: A vehicle containing 0.6% sodium carboxymethyl cellulose (SCMC) was suitable for the preparation of ATV extemporaneous oral suspension. The HPLC method was found to have linearity covering the range of 10–100 mg/ml with a correlation coefficient (r) greater than 0.99. Accuracy and precision were in the range of 99–110% and below 11 %RSD, respectively. The pH and viscosity of the developed formulation stored under ambient and refrigerated temperatures did not differ over 7 d, while the re-dispersibility time of the formulation stored in refrigerator shifted to higher more slowly than the formulation stored at ambient temperature. The % ATV remaining over 7 d was 92.02–106.67% at 30±2 °C and 99.64–107.58% at 4±2 °C. After being subjected to stress conditions, ATV remained stable under oxidation and alkaline conditions, while it significantly degraded under acidic conditions, remaining 24.27%. Conclusion: The developed ATV extemporaneous oral suspension using a suspension vehicle containing 0.6% SCMC was chemically stable for at least 7 d at 30±2 °C and 4±2 °C. However, this formulation should be preferably stored at refrigerator temperature for use within 7 d to maintain both chemical and physical stability. The formulation was not stable under acid-stress conditions.